The relationship between pasture degradation and soil properties in the Brazilian amazon: a case study - Muller, MML; Guimaraes, M. F.; Desjardins, T.; Mitja, D. (Elsevier B.V., 2004)
Pasture degradation is one of the greatest problems related to land use in the Amazon region, forcing farmers to open new forest areas. Many studies have identified the causes and the factors involved in this degradation process, in an attempt to reverse the situation. The purpose of this study was to examine the relationship between pasture degradation and some soil properties, to try to identify the most significant soil features in the degradation process. A cattle raising farm in the eastern Amazon region, with pastures of different ages and degrees of degradation, was used as the site for this study: a primary forest area, PN; three Guinea grass (Panicum maximum Jacq.) pastures in an increasingly degraded sequence-P1, P2 and P3; one Gamba grass (Andropogon gayanus Kunth) pasture following an extremely degraded Guinea grass pasture, P4. Aboveground phytomass data showed differences between the pastures, reflecting initially observed degradation levels. Grass biomass decreased sharply from P1 to P2 and disappeared at P3. Pasture recovery with Gamba grass at P4 was very successful, with grass biomass higher than P1 and weed biomass smaller than P2 and P3. Root biomass also decreased with pasture degradation. Soil bulk density increased with pasture decrease at the topsoil layer. Results from the soil chemical analysis showed that there were no signs of decrease in organic carbon and total nitrogen after the forest was transformed into pasture. In all pastures, degraded or not, the soil pH, the sum of bases and the saturation degree were higher than in the forest soil. The extractable phosphorus content, lower in forest soil, remained quite stable in pasture soils, but it could become a limiting factor for the maintenance of Guinea grass. Results indicated that pasture degradation does not seem to be directly related to the modification of the chemical features of soils. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Amazonia; deforestation; biomass; Panicum maximum; phosphorus; roots